PRACTICES REGARDING PALLIATIVE CARE AMONG NURSES WORKING AT TERTIARY CARE HOSPITAL, PUNJAB PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Palliative care nursing plays a vital role in providing compassionate and holistic care to individuals facing life-limiting illnesses. It focuses on enhancing the quality of life for patients and their families by addressing physical, emotional, social, and spiritual needs. Nurses are at the forefront of palliative care, offering support and comfort throughout the disease trajectory. This study aims to assess the actual practices of nurses in delivering palliative care, examining the extent to which they integrate palliative care principles into their daily routines in ICU, HDU and Oncology settings. A cross-sectional research design was used to assess practices of nurses regarding palliative care in ICU, HDU, and Oncology Department at tertiary care hospital in Punjab Pakistan. Target population of this study included the Registered Nurses working in ICU, HDU and oncology Sample size was calculated through software Open epi. 55 Registered  nurses fulfilling the inclusion criteria were included in this study selected through purposive sampling technique. The data was collected through an adaptive questionnaire consisting of a consent form, a demographic sheet and 12 items regarding practices of palliative care. The data analyzed through SPSS version 27. Out of 55 participating nurses, 29.1% were male and 70.9% were female. The majority (58.2%) were aged 30–40 years. Regarding practices, 72.7% demonstrated good practices, whereas 27.3% had poor practice levels. These findings indicate that majority of nurses had good practices regarding palliative care.